Optimization of computer labs usage in schools: a case study of smart-school - Maarof, Mohd. Aizaini; Ismail, Abd. Samad; Salleh, Mazleena; Kadir, Rashidah; Zainal, Anazida (Fakulti Sains Komputer & Sumber Maklumat, 2007)
The explosion of computer-based multimedia instructional has led to the adoption of general applications, such as word-processors and spreadsheets as an efficient way of learning. Furthermore, with the explosion of Internet Communication Technology (ICT) and a catalyst program like Multimedia Super Corridor (MSC), where smart school is one of the agenda, conventional classrooms nationwide are being transformed to a PC-based laboratory. With the future stakes of children nationwide, the matter of controlling and providing the best environment for study cannot be taken lightly. This project developed a Smart Laboratory Real-Time Management System (SLRTMS), to further increase the efficiency of learning, management and student monitoring by using client-server approach. This system will benefit both the instructor and the student, as it simplifies common tasks in a normal PC-based classroom. The server, which is used by the instructor as a control device for teaching and communicating, provides several functions: automating class attendance; broadcasting laboratory work and announcement; providing discussion channel between instructor and students; viewing and locking computer screens; and generating database reports. SLRTMS is a LAN-based system using Windows 98 as the platform and it’s development exploited the functionality of COM and DCOM while using Microsoft Access as its database.